Which start-ups win public procurement tenders? - Bastian Krieger; Lena Füner; Malte Prüfer (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
We explore which start-ups win in public procurement. Most notably, our analysis presents significant differences between firms applying for tenders with and without functional criteria. First, we use representative telephone survey data to estimate public procurement applicant and winner shares for the population of German start-ups. We find in total eleven percent of start-up firms applied for public tenders since their foundation, and 65 percent of them won at least one tender. Additionally, younger and more innovative firms tend to apply for and win tenders with functional criteria, while older and less innovative firms tend to apply for and win tenders without functional criteria. Second, we employ non-linear estimation methods to identify firm and founder characteristics predicting to win public tenders within the group of applicants. Start-ups applying for functional tenders profit from smaller foundation teams, younger founders, more industry experience, and higher innovation capacities, while start-ups applying for tenders without functional criteria, profit from larger foundation teams, older founders, more industry experience, and the absence of founding experience
Keywords: H57; L26; O38; 330; Public procurement; Start-up firms; Innovation